Investigation of acidic chemical recycling of poly(acetal-ester)s - Vesterbacka,Saga (2023)
Plastic recycling is a very relevant topic from both environmental and economic viewpoints. Chemical plastic recycling is a logical solution to the plastic problems, which shows the potential to reduce plastic waste and carbon emissions from burning the plastics. One strategy of chemically recycling plastic is to incorporate sensitive bonds into polymer chains, which can be selectively degraded under specific conditions. In this study, selective acetal hydrolysis of two poly(acetal-esters)s containing spiroacetal linkage was performed under different conditions regarding temperature, concentrations of acid, and additional solvents. More specifically, polymers with spiroacetal groups have been hydrolyzed, which include: Akestra 90, Akestra 110, PHVT-5 and PHVT-20. The experiments have been mainly analyzed with NMR spectroscopy. The results show that both Akestra 90 and Akestra 110 are very resistant to hydrolysis. However, PHVT-5 and PHVT-20 could be completely hydrolyzed. There was then an attempt to re-polymerize the oligomer of PHVT-5 which led the polymer to be polymerized to 79 %.
Keywords: Poly(actetal-ester)s; Chemical plastic recycling; Hydrolysis; Acidic degradation; Akestra; PHVT; Re-polymerization; Polymer technology